Female subjects in black and white: Race, psychoanalysis, feminism - Abel, Elizabeth; Christian, Barbara; Moglen, Helene (University of California Press, 1997)
This landmark collaboration between African American and white feminists goes to the heart of problems that have troubled feminist thinking for decades. Putting the racial dynamics of feminist interpretation center stage, these essays question such issues as the primacy of sexual difference, the universal nature of psychoanalytic categories, and the role of race in the formation of identity. They offer new ways of approaching African American texts and reframe our thinking about the contexts, discourses, and traditions of the American cultural landscape. Calling for the racialization of whiteness and claiming that psychoanalytic theory should make room for competing discourses of spirituality and diasporic consciousness, these essays give shape to the many stubborn incompatibilities―as well as the transformative possibilities―between white feminist and African American cultural formations. Bringing into conversation a range of psychoanalytic, feminist, and African-derived spiritual perspectives, these essays enact an inclusive politics of reading. Often explosive and always provocative, Female Subjects in Black and White models a new cross-racial feminism.
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; femmes* afro-américaines; féminismes noirs; littérature; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences humaines; états-unis; études littéraires

Moi, Tituba sorcière --: noire de Salem - Condé, Maryse; De Serres, Murielle; Thérien, Michel; Jean, Julie (Littératures et cultures, 1995)
Fille d'une esclave violée par un marin anglais à bord d'un vaisseau négrier, Tituba, née à la Barbade, est initiée aux pouvoirs surnaturels par Man Yaya, guérisseuse et faiseuse de sorts. Son mariage avec John Indien l'entraîne à Boston puis au village de Salem, au service du révérend Samuel Parris. Elle est emprisonnée à la suite du procès des sorcières de Salem en 1692.
Keywords: afro-féminisme; amériques; approches et analyses; arts; barbade; caraïbes; cours; discipline; féminismes noirs; histoire et politique; lit2815; premier cycle; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; états-unis; études littéraires

Black women, writing, and identity: Migrations of the subject - Boyce Davies, Carole (Routledge, 1994)
Black Women Writing and Identity is an exciting work by one of the most imaginative and acute writers around. The book explores a complex and fascinating set of interrelated issues, establishing the significance of such wide-ranging subjects as: * re-mapping, re-naming and cultural crossings * tourist ideologies and playful world travelling * gender, heritage and identity * African women's writing and resistance to domination * marginality, effacement and decentering * gender, language and the politics of location Carole Boyce-Davies is at the forefront of attempts to broaden the discourse surrounding the representation of and by black women and women of colour. Black Women Writing and Identity represents an extraordinary achievement in this field, taking our understanding of identity, location and representation to new levels.
Keywords: afro-féminisme; approches et analyses; cours; discipline; fem1000; femmes* noires; féminismes noirs; littérature; premier cycle; ressource en ligne; thématiques; écriture des femmes*; études littéraires; études postcoloniales

Yearning: Race, gender, and cultural politics - hooks, bell (Between the Lines, 1990)
Pour bell hooks, la meilleure critique culturelle ne voit pas la nécessité de séparer la politique du plaisir de lire. Yearning rassemble certains des classiques et des premiers morceaux de critique culturelle de hooks des années 80. Abordant des sujets tels que la pédagogie, le postmodernisme et la politique, hooks examine une variété d'artefacts culturels, du film Do the Right Thing de Spike Lee et du film Wings of Desire de Wim Wenders aux écrits de Zora Neale Hurston et Toni Morrison. Le résultat est une collection poignante d'essais qui, comme tout le travail de hooks, s'intéresse avant tout à la transformation des structures oppressives de domination.
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; lit4700; littérature; premier cycle; périodes historiques; régions géographiques; théories culturelles; états-unis; études littéraires